Unmanned/Unattended Sensors and Sensor Networks 2004
DOI: 10.1117/12.578300
|View full text |Cite
|
Sign up to set email alerts
|

Optical bistable devices as sensing elements

Abstract: The nonlinear optical properties of many materials and devices have been the main object of research as potential candidates for sensing in different places. Just one of these properties has been, in most of the cases, the basis for the sensing operation. As a consequence, just one parameter can be detected. In this paper, although just one property will be employed too, we will show the possibility to sense different parameters with just one type of sensor. The way adopted in this work is the use of the optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our experimental studies show that the photocarriers are induced mainly by the linear optical absorption in the device. The proposed approach can be exploited to design ultralow power optical transistors, optical memory elements, and ultrasensitive sensors [19][20][21][22]. In addition to its contribution to heat generation, the photocurrent can be monitored in an external electronic circuit to generate a negative feedback signal (i.e., adjusting the reverse bias voltage) to stabilize the bistable features against the random variations of the environmental conditions (e.g., temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Our experimental studies show that the photocarriers are induced mainly by the linear optical absorption in the device. The proposed approach can be exploited to design ultralow power optical transistors, optical memory elements, and ultrasensitive sensors [19][20][21][22]. In addition to its contribution to heat generation, the photocurrent can be monitored in an external electronic circuit to generate a negative feedback signal (i.e., adjusting the reverse bias voltage) to stabilize the bistable features against the random variations of the environmental conditions (e.g., temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done in DFB, and FP-LAS. We have presented some studies on this direction, with difference approaches, that can be found on references [2,[6][7]. Here we concentrate our analysis on the use of VCSOA.…”
Section: Semiconductor Laser Amplifiers Bistability As Sensing Elementmentioning
confidence: 99%